Role of GRK2 in Trophoblast Necroptosis and Spiral Artery Remodeling: Implications for Preeclampsia Pathogenesis - Lv, Zi; Xiong, Li-ling; Qin, Xian; Zhang, Hua; Luo, Xin; Peng, Wei; Kilby, Mark D.; Saffery, Richard; Baker, Philip N.; Qi, Hong-bo (Frontiers in Cell and Developmental Biology, 2021)
Impaired invasion of extravillous trophoblasts and severe oxidative stress manifest the poor placentation in preeclampsia, which is life-threatening and more than a hypertensive disease of pregnancy. Previous studies have reported that G protein-coupled receptor kinases (GRKs) play a key role in initiating hypertension and hypertensive renal damage, yet little evidence so far suggests a link between GRKs and preeclampsia-related hypertension. Here, we demonstrate GRK2 expression is significantly downregulated (P<0.0001) in preeclamptic placentas compared to normotensive controls. Knockdown or inhibition of GRK2 in placentas caused insufficient arterial remodeling and elevated trophoblast necroptosis in vivo. These further induced preeclampsia-like phenotype in mice: hypertension, proteinuria, and elevated pro-angiogenic cytokines. By human extra-villous invasive trophoblast cell line (HTR8/SVneo cells), we revealed the knockdown or inhibition of GRK2 triggered excessive death with typical necroptotic characteristics: nuclear envelope rupture and the activation of RIPK1, RIPK3, and MLKL. Necrostatin-1, an inhibitor of RIPK1, is able to restore survival of trophoblasts. Together, our findings demonstrated that insufficient GRK2 activity compromises spiral artery remodeling and initiates necrotic events in placentas, thereby leading to preeclampsia. These findings advance our understanding of GRK2 in the pathogenesis of preeclampsia and could shed light on a potential treatment for preeclampsia.